2010
DOI: 10.1111/j.1743-6109.2009.01499.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Partner Satisfaction after AMS Inflatable Penile Prosthesis Implant

Abstract: Introduction The implantation of penile prostheses is an effective option for treating erectile dysfunction (ED), and nowadays it is used to treat those cases where pharmacological agents have not provided a useful result. Aims The primary aim of the present study was to verify the patient and their partner’s satisfaction, in 80 patients who underwent AMS CX 700 prostheses implant in a single center, by the same surgeon, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
64
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 16 publications
6
64
0
Order By: Relevance
“…Previous studies have reported that the majority of patients are satisfied with their penile implants. 3 However, this study shows that despite Patient discomfort or dissatisfaction is usually seen in patients who are not properly informed of these potential complications prior to the procedure. Tefilli et al analyzed the psychosexual aspect of IPP replacement and noted that the factors that improved sexual experiences were penile rigidity and how rapid the prosthesis could provide erection.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Previous studies have reported that the majority of patients are satisfied with their penile implants. 3 However, this study shows that despite Patient discomfort or dissatisfaction is usually seen in patients who are not properly informed of these potential complications prior to the procedure. Tefilli et al analyzed the psychosexual aspect of IPP replacement and noted that the factors that improved sexual experiences were penile rigidity and how rapid the prosthesis could provide erection.…”
Section: Discussionmentioning
confidence: 71%
“…1,2 The majority of patients who undergo IPP replacement are satisfied with the results and do not require further attention. 3 Surgical re-implantation of IPP devices has been shown to cause greater morbidity and intra-operative complications than initial implantation. 1,4 However, patient satisfaction after reimplantation and revision has not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Even though patient and partner satisfaction is as high as 97% after penile prosthesis implantation, important complications seen in the perioperative and postoperative periods show that prosthesis implantation is a critical operation (4,5,6). The most important complications seen in the perioperative period is related to the urethra, bladder and bowel.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment, as third-line therapy, can be performed after failure of all other options. Penile prosthesis implant, although invasive, has reached high levels of satisfaction and is associated with better sexual function, perception and with patient and partner' s high gratification (6,7). Complications related to mechanical failure of prosthesis, space for the reservoir (filled with 100 mL of saline solution), posterior to transversalis fascia in cephalad to caudal position (Figures 5, 6), is created.…”
Section: Introductionmentioning
confidence: 99%